Isolation of naringin and neohesperidin from Citrus grandis (L) Osbeck (Family Rutaceae) - Buenavista, Cherry Maria G. (Manila College of Pharmacy, University of the Philippines, 1985)
Flavanone glycosides, naringin and neohesperidin were isolated from the methanol extract of the inner portion or albedo or the rind of Citrus grandis (Linne) Osbeck. The separation of these two constituents from each other was done by repeated extraction fo the crude methanol extract with chloroform, separating the neohesperidin in the chlorofrom extract from naringin which is retained in the original methanol extract. Naringin occurs as colorless needle-like crystals and colors violet with Ferric Chloride. Neohesperidin occurs as yellowish scaly crystals and colors yellow in thin-layer chromatography plates when sprayed with Ferric Chloride. Thin layer chromatography was done to distinguish naringin from neohesperidin.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, October 1985.
Keywords: Citrus; Pummelo; Lukban; Suha